ADAM17 cytoplasmic domain modulates Thioredoxin-1 conformation and activity - e Costa, Rute A.P. (Redox Biol, 2020)
The activity of Thioredoxin-1 (Trx-1) is adjusted by the balance of its monomeric, active and its dimeric, inactive state. The regulation of this balance is not completely understood. We have previously shown that the cytoplasmic domain of the transmembrane protein A Disintegrin And Metalloprotease 17 (ADAM17cyto) binds to Thioredoxin-1 (Trx-1) and the destabilization of this interaction favors the dimeric state of Trx-1. Here, we investigate whether ADAM17 plays a role in the conformation and activation of Trx-1. We found that disrupting the interacting interface with Trx-1 by a site-directed mutagenesis in ADAM17 (ADAM17cyto(F730A)) caused a decrease of Trx-1 reductive capacity and activity. Moreover, we observed that ADAM17 overexpressing cells favor the monomeric state of Trx-1 while knockdown cells do not. As a result, there is a decrease of cell oxidant levels and ADAM17 sheddase activity and an increase in the reduced cysteine-containing peptides in intracellular proteins in ADAM17cyto overexpressing cells. A mechanistic explanation that ADAM17cyto favors the monomeric, active state of Trx-1 is the formation of a disulfide bond between Cys(824) at the C-terminal of ADAM17cyto with the Cys(73) of Trx-1, which is involved in the dimerization site of Trx-1. In summary, we propose that ADAM17 is able to modulate Trx-1 conformation affecting its activity and intracellular redox state, bringing up a novel possibility for positive regulation of thiol isomerase activity in the cell by mammalian metalloproteinases.